Performance Evaluation of Small-Scale Irrigation Scheme: A Case Study of Temsa Small Scale Irrigation Scheme of Goma District, Jimma Zone, South West Ethiopia - Etefa Tilahun; Minda Tadesse; Hewan Tadesse; Addisu Asefa (Air, Soil and Water Research)
A study was carried out from November to May in the cropping season of 2016E.C to evaluate the performance of Temsa small scale irrigation scheme. Both internal and external indicators were considered for evaluation. The internal indicator efficiencies such as conveyance, application, storage, distribution uniformity, and deep percolation ratio and the external indicators such as agricultural output, water supply, water delivery capacity, physical, and economic and financial indicators were evaluated. The result reveals that, the average conveyance efficiency of the main, secondary, and tertiary canals were 79.6%, 85.6%, and 84.7%, respectively. The scheme has on average application efficiency (Ea), storage efficiency, deep percolation ratio, and distribution uniformity of 40.87%, 78.04%, 59.70%, and 93.33%, respectively. The poor Ea and low conveyance efficiency of the canal affected the overall scheme performance. The result reveals that, the overall efficiency of the scheme was 23.19%. The four basic agricultural output indicators of the scheme such as output per unit irrigated area, output per unit command area, output per unit irrigation diverted, and output per unit water consumed were 4,738.58 US$/ha, 1,176.08 US$/ha, 1.16 US$/m 3 , and 0.89 US$/m 3 , respectively. This shows that, the command area was beneficial and was giving a revenue for the farmers at the cropping season. The relative irrigation supply and the water delivery capacity of the canal were 2.37 m 3 and 83%, respectively. In the current study, the irrigation ratio and the sustainability of the irrigated area were 0.25 and 0.43, respectively. The irrigation ratio was low due to the designing problem. Availability of water throughout the year and market accessibility near the scheme were the advantage of the scheme that encourage the farmers. However, the input costs were affecting the return obtained from the product. Hence it is better to provide access to credit for the sustainable production and improve the farmers income.